2008
DOI: 10.1038/sj.ejhg.5201989
|View full text |Cite
|
Sign up to set email alerts
|

The Tunisian population history through the Crigler–Najjar type I syndrome

Abstract: Crigler-Najjar syndrome type I (CN-I) is a rare and severe metabolic disorder. A recurrent mutationc.1070A4G in exon 3 -was identified in the Tunisian population, suggesting a founder effect. In 2004, the detection of this mutation in two Kuwaiti Bedouin families has called the Tunisian founder effect in question again. To determine the origin of this mutation, 21 Tunisian and 2 Kuwaiti Bedouin CN-I patients were screened using nine genetic markers. Haplotype analysis confirmed the founder effect hypothesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…The child was then discharged with at-home phototherapy and regular followup. Molecular study showed that the child was homozygous for the c.1070A > G mutation within exon 3 of the UGT1A1 gene, a previously reported mutation in CN-I patients (Petit et al 2008) thus confirming the diagnosis of CN-I syndrome.…”
Section: Case Reportsupporting
confidence: 69%
“…The child was then discharged with at-home phototherapy and regular followup. Molecular study showed that the child was homozygous for the c.1070A > G mutation within exon 3 of the UGT1A1 gene, a previously reported mutation in CN-I patients (Petit et al 2008) thus confirming the diagnosis of CN-I syndrome.…”
Section: Case Reportsupporting
confidence: 69%
“…Founder mutations observed in Tunisia were also reported in populations from the Middle East such as the splice site mutation in the CA II gene responsible for carbonic anhydrase II deficiency in the Arabic peninsula [47] and the p.Q357R molecular defect in the UGT1A1 gene of the Crigler-Najjar type I syndrome in the Kuwaiti population [48]. In other cases, founder mutations are dispersed around the Mediterranean basin as illustrated by the c.744delA mutation in the TTPA gene of ataxia with isolated vitamin E deficiency [49] and the splice site defects in megaloblastic anemia 1 [50] and triple-A syndrome [51].…”
Section: Resultsmentioning
confidence: 99%
“…These mutations likely arose in the Middle East and were introduced in Tunisia following Banu Hilal invasions that settled in the Maghreb in the eleventh century. Several other mutations like those responsible for carbonic anhydrase and Crigler Najjar disease were introduced similarly [47,48]. The extent of geographic repartition of a founder mutation could give insights into its history and age.…”
Section: Discussionmentioning
confidence: 99%
“…Crigler Najjar syndrome type I and Xeroderma pigmentosum (XP) group C are caused by the founder mutations p.Q357R and p.V548AfsX25, respectively [19][20][21] , that are shared with other Mediterranean populations. In other cases, some allelic heterogeneity is responsible for the expression of the morbid phenotype, with a predominant founder mutation as the major cause of the disease along with rare familial private molecular lesions.…”
Section: Founder Effect Consanguinity and Genetic Disease Frequencymentioning
confidence: 99%